2018
DOI: 10.4266/acc.2018.00136
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation Index in the First 24 Hours after the Diagnosis of Acute Respiratory Distress Syndrome as a Surrogate Metric for Risk Stratification in Children

Abstract: BackgroundThe diagnosis of pediatric acute respiratory distress syndrome (PARDS) is a pragmatic decision based on the degree of hypoxia at the time of onset. We aimed to determine whether reclassification using oxygenation metrics 24 hours after diagnosis could provide prognostic ability for outcomes in PARDS.MethodsTwo hundred and eighty-eight pediatric patients admitted between January 1, 2010 and January 30, 2017, who met the inclusion criteria for PARDS were retrospectively analyzed. Reclassification based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…Remarkably, the C RS of C-PARDS was close to the C RS reported in other pediatric cohorts of viral PARDS 31 and other restrictive lung diseases 38 . Regarding outcomes, mortality was not statistically different between C-PARDS and MIS-PARDS.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Remarkably, the C RS of C-PARDS was close to the C RS reported in other pediatric cohorts of viral PARDS 31 and other restrictive lung diseases 38 . Regarding outcomes, mortality was not statistically different between C-PARDS and MIS-PARDS.…”
Section: Discussionsupporting
confidence: 84%
“…39,40 It is very interesting that in the current study, previous known variables associated with mortality in PARDS and in pediatric critical COVID-19, like organ failures and hypoxemia severity, were not different between survivors and non-survivors. 37,38,[41][42][43][44][45] A surprising result was the difference in the respiratory mechanics between the clinical phenotypes. The cohort fulfilled PARDS and critical COVID-19 criteria but with different characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric patients with ARDS differ from adult patients with ARDS in terms of characteristics such as etiologic factors, pathophysiology, clinical course, and outcomes. [1][2][3][4][5][6][7] Since ARDS was first described in 1967, 8 numerous studies have been performed addressing various clinical issues including definitions, diagnostic criteria, classification, risk factors for mortality, and therapeutic strategies to improve clinical outcomes. [9][10][11][12][13][14][15][16] However, such investigations have mainly addressed adult ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…The PALICC definition is unclear as to when to stratify hypoxemia severity: at the time of or following PARDS diagnosis 9,25–28 . The PARDIE study 9 suggested that hypoxemia severity stratification at 6 h after PARDS diagnosis could better discriminate pediatric mortality while other studies 25–28 had advocated waiting for 12–24 h after PARDS diagnosis for hypoxemia severity stratification. The PALICC definition recommends OI measurements at the onset of PARDS and at 24, 48, and 72 h after onset, but superiority was not evaluated 15,25 .…”
Section: Discussionmentioning
confidence: 99%